2014
DOI: 10.1016/j.biopha.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl-l-cysteine sensitizes pancreatic cancers to gemcitabine by targeting the NFκB pathway

Abstract: First-line therapy for pancreatic cancer is gemcitabine. Although tumors may initially respond to the gemcitabine treatment, soon tumor resistance develops leading to treatment failure. Previously, we demonstrated in human MIA PaCa-2 pancreatic cancer cells that N-acetyl-l-cysteine (NAC), a glutathione (GSH) precursor, prevents NFκB activation via S-glutathionylation of p65-NFκB, thereby blunting expression of survival genes. In this study, we documented the molecular sites of S-glutathionylation of p65, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…While single dose administration of NAC or gemcitabine failed to inhibit the growth of MiaPaca2 xenograft tumors in male athymic mice, combination of both agents reduced tumor growth by about 50%. Again, in this setting, activation of NF-κB was attenuated [130]. Finally, both vitamin E and resveratrol have been shown to amplify the anti-tumorigenic effects of gemcitabine in pancreatic cancer cells and in both xenograft and orthotopic MiaPaca2 mouse models of PDA in a manner that was dependent on the inhibition of NF-κB activity [131,132].…”
Section: Targeting Ros In Pda Development and Progressionmentioning
confidence: 99%
“…While single dose administration of NAC or gemcitabine failed to inhibit the growth of MiaPaca2 xenograft tumors in male athymic mice, combination of both agents reduced tumor growth by about 50%. Again, in this setting, activation of NF-κB was attenuated [130]. Finally, both vitamin E and resveratrol have been shown to amplify the anti-tumorigenic effects of gemcitabine in pancreatic cancer cells and in both xenograft and orthotopic MiaPaca2 mouse models of PDA in a manner that was dependent on the inhibition of NF-κB activity [131,132].…”
Section: Targeting Ros In Pda Development and Progressionmentioning
confidence: 99%
“…Nuclear factor-κB (NF-κB) plays a critical role in the development and progression of various human cancers that exhibit constitutive and continuous NF-κB activity (17,18). However, the induction of this signaling pathway is also associated with gemcitabine chemoresistance in PC cells (19)(20)(21). We thus reasoned that agents that block NF-κB activation may reduce chemoresistance to gemcitabine, and may be effective when used in combination with gemcitabine as a novel therapeutic regimen for treating PC.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar attempt towards the management of oral cancer, Lee et al demonstrated that intraperitoneal treatment of human tongue squamous carcinoma xenografts with NAC significantly reduced mean tumor volume by 33% [ 36 ]. In a recent study by Qanungo et al, while single agent chemotherapy with the first-line agent gemcitabine failed to inhibit pancreatic cancer growth, adjunct treatment with intraperitoneal NAC reduced tumor growth [ 37 ]. Sayin et al, however, reported that supplementing the diet with NAC and vitamin E increased tumor progression in mouse models of B-RAF- and K-RAS-induced lung cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%